A phase 2 study of mocetinostat, a histone deacetylase inhibitor, in relapsed or refractory lymphoma. (25th April 2017) - Batlevi, Connie L.; Crump, Michael; Andreadis, Charalambos; Rizzieri, David; Assouline, Sarit E.; Fox, Susan; van der Jagt, Richard H. C.; Copeland, Amanda; Potvin, Diane; Chao, Richard; Younes, Anas
Summary: Deregulation of histone deacetylase (HDAC) is important in the pathogenesis of follicular lymphoma (FL) and diffuse large B‐cell lymphoma (DLBCL). Mocetinostat, an isotype‐selective HDAC inhibitor, induces accumulation of acetylated histones, cell cycle arrest and apoptosis in several cancers. This phase 2 study evaluated mocetinostat in patients with relapsed/refractory (R/R) DLBCL and FL. Seventy‐two patients received mocetinostat (starting doses: 70–110 mg TIW, 4‐week cycles). The best overall response rate (95% CI) was 18·9% (7·2, 32·2) for the DLBCL cohort ( n  = 41), and 11·5% (1·7, 20·7) for the FL cohort ( n  = 31). Responses were durable (≥90 days in 7 of 10 responses). Overall, 54·1% and 73·1% of patients derived clinical benefit (response or stable disease) from mocetinostat in the DLBCL and FL cohorts, respectively. Progression‐free survival ranged from 1·8 to 22·8 months and 11·8 to 26·3 months in responders with DLBCL and FL, respectively. The most frequent treatment‐related adverse events were fatigue (75·0%), nausea (69·4%) and diarrhoea (61·1%). Although mocetinostat had limited single‐agent activity in R/R DLBCL and FL, patients with clinical benefit had long‐term disease control. The safety profile was acceptable. This drug class warrants further investigation, including identifying patients more likely to respond to this agent, or in combination with other agents.